A Cross Sectional Study on the Effect of Stress and Academic Stressors Among International Medical Students of a Romanian University - Hotoleanu, Cristina; Hotoleanu, Andrei (European Scientific Journal, ESJ, 2021)
Medical students are exposed to increased stress due to academic, psycho-social and health-related factors. This study aimed to assess the levels of stress and the associations with socio-demographic characteristics and academic performance; the frequency of the major academic stressors; the most stressful factors as stated by the students themselves. A cross-sectional study including 110 international medical students of the 3rd-year was performed in the first two weeks of November 2019. A questionnaire including socio-demographic data, a list with potential academic stressors and an open question regarding the greatest stressors in student’s opinion as well as The Kessler Psychological Distress Scale, was administrated in pen-andpaper format. Mild, moderate and severe levels of stress were found in 36.73%, 22.44 %, and 13.26 % of students, respectively. Increased levels of stress were associated with poor academic performance and did not correlate with age or country of origin. The frequency of moderate and severe stress was 3-times greater in women than in men. The most stressful factors in students’ opinion were the academic stressors (88.77%) followed by psychosocial factors (25.51%) and health-related factors (9.18%). The frequency of examination was perceived as a stressor always present by more than 25% of the students. Most of the students showed elevated levels of stress. Academic factors were the most important stressors in students’ opinion. Further research is needed to identify the proper strategy to rectify academicrelated problems to decrease the levels of stress.